Mixed-mode fracture assessment of largely deformable hyperelastic materials highlighting crack removal phenomenon - Kazemi, Mehdi; Heydari-Meybodi, Mahdi; Petru, Michal; Ayatollahi, Majid R. (Elsevier, 2024)
Due to the special mechanical characteristics, rubbers are nowadays utilized in various industries. In this research, the effect of an existing crack on the behavior of Nitrile Butadiene Rubber (NBR) filled with Carbon Black (CB), which has shown high deformability, is investigated experimentally, numerically and analytically under mixed-mode (I/II) loading. It is observed experimentally that in the cracked largely deformable rubbers, after the initial crack blunting, the crack is nearly removed and the specimen is deformed in such a way that almost no sign of stress concentration factor exists in the sample. Thus, the rupture of these rubbers is divided into two separate phases; named here as the crack removal phase and the final rupture phase, and for each separate phase, a distinct criterion is developed to assess the fracture of cracked rubbers. The good agreement between the theoretical predictions based on each criterion and the corresponding experimental data confirms the very good accuracy of the presented criteria. The independence of critical J-integral value (Jc) J c ) from the mode mixity is also investigated.
Keywords: Hyperelastic materials; Fracture criterion; Crack removal phase; Largely deformable rubber; Mixed-mode (I/II) loading